Global Governance Dimensions of Globally Networked Risks: The State of the Art in Social Science Research. Issue 1 (March 2017) - Galaz, Victor; Tallberg, Jonas; Boin, Arjen; Ituarte‐Lima, Claudia; Hey, Ellen; Olsson, Per; Westley, Frances
Abstract : Global risks are now increasingly being perceived as networked, and likely to result in large‐scale, propagating failures and crises that transgress national boundaries and societal sectors. These so called "globally networked risks" pose fundamental challenges to global governance institutions. A growing literature explores the nature of these globally networked or "systemic" risks. While this research has taught us much about the anatomy of these risks, it has consistently failed to integrate insights from the wider social sciences. This is problematic since the prescriptions that result from these efforts flow from naїve assumptions about the way real‐world state and non‐state actors behave in the international arena. This leaves serious gaps in our understanding of whether networked environmental risks at all can be governed. The following essay brings together decades of research by different disciplines in the social sciences, and identifies five multi‐disciplinary key insights that can inform global approaches to governing these. These insights include the influence of international institutions; the dynamics and effect of international norms and legal mechanisms; the need for international institutions to cope with transboundary and cross‐sectoral crises; the role of innovation as a strategy to handle unpredictable global risks; and the necessity to address legitimacy issues.